Tingkat Pengetahuan dan Sikap Ilmiah Kelas X Melalui Model Kontekstual Berbasis Proses Budidaya Fungi - Mahendra, Bimo; Evi Hanizar; Sarwo Danuji (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effect of implementing a contextual learning model based on the fungal cultivation process on improving the knowledge and scientific attitudes of Grade X science students at MA Miftahul Ulum Suren in the 2024/2025 academic year. The method used is a quantitative approach with a quasi-experimental design of the Posttest Only Control Design type. The research subjects consisted of two classes: the experimental class with 20 students and the control class with 20 students. The experimental class received instruction using a process-based contextual learning model, while the control class was taught using conventional methods. Data collection instruments included a posttest consisting of 10 essay questions to measure knowledge and an observation sheet to assess students' scientific attitudes. The results showed that the average knowledge level in the experimental class reached 82.5%, while the control class only achieved 71%. Regarding scientific attitudes, the experimental class scored an average of 3.8 (categorized as very good), whereas the control class scored 2.9 (categorized as good). In conclusion, the process-based contextual learning model is more effective in improving students’ knowledge and scientific attitudes, as it links learning materials to real-life contexts, encourages active student engagement, and fosters critical thinking and scientific skills. Keywords: Fungal Cultivation, Knowledge, Process-Based Contextual Learning, Scientific Attitudes